Feeding ecology of the longtail southern cod, Patagonotothen ramsayi (Regan, 1913) (Notothenioidei) in the Marine Protected Area Namuncurá-Burdwood Bank, Argentina - Fischer, Luciana Stefania; Covatti Ale, Marina; Deli Antoni, Mariana Yanel; Díaz de Astarloa, Juan Martín; Delpiani, Gabriela Elina (Polar Biology)
Patagonotothen ramsayi has the highest concentrations at Burdwood Bank, playing a key ecological role in the demersal food web. The aim of this study was to describe and analyze the feeding ecology of longtail southern cod in the Marine Protected Area Namuncurá-Burdwood Bank (MPAN-BB). From 369 specimens sampled, 229 (62.06%) contained food. Prey-specific index of relative importance (%PSIRI) for each prey was calculated showing that P. ramsayi preyed mainly on polychaetes (21.07%), amphipods (14.89%), other crustaceans (13.25%), and decapods (11.62%). The analysis of the feeding strategy confirms that P. ramsayi is a generalist feeder. The effect of sex, ontogenetic stage, total length (TL), and capture depth was evaluated using generalized linear models. All prey categories were independent of sex, while a differential consumption of isopods and polychaetes according to the ontogenetic stage was observed. Isopods were more consumed by juveniles, while polychaetes were fed by adults. The intake of amphipods and decapods was not influenced by any of the studied variables. Regarding capture depth, the consumption of euphausiids and polychaetes was higher in shallower areas, in contrast to teleost and isopods that were more ingested at greater depths. Finally, the intake of euphausiids, teleosts, and polychaetes was positively influenced by the total length of the predator, while the consumption of other invertebrates was negatively related. It may be concluded that Patagonotothen ramsayi in the MPAN-BB has a generalist diet and demersal-benthic feeding habits, changing its diet with total length and depth of capture. Fil: Fischer, Luciana Stefania. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Covatti Ale, Marina. Consejo Nacional de Investigaciones ...